Early Initiation of Breastfeeding (EIBF) Practices in Bener Meriah Regency, Aceh, Indonesia: A Cross-Sectional Study on the Role of Midwives in Reducing Infant Mortality - Irdayani; Widya Apriani; Hida Yana (HM Publisher, 2024)
Early initiation of breastfeeding (EIBF) is critical for reducing infant mortality and improving child health outcomes. Midwives play a crucial role in promoting and supporting EIBF. This study investigated EIBF practices in Bener Meriah Regency, Aceh, Indonesia, focusing on the factors associated with midwives' knowledge, attitudes, and practices regarding EIBF. A cross-sectional study was conducted among 150 midwives in Bener Meriah Regency. Data were collected using a structured questionnaire that included items on sociodemographic characteristics, knowledge, attitudes, and practices related to EIBF. Descriptive statistics, chi-square tests, and logistic regression were used to analyze the data. The majority of midwives (87.3%) had good knowledge about EIBF. However, only 62.7% of midwives reported always assisting mothers with EIBF within one hour of birth. Factors significantly associated with midwives' EIBF practices included their age, years of experience, and place of work (urban vs. rural). While midwives in Bener Meriah Regency generally possess adequate knowledge about EIBF, there is a need to improve their practices in assisting mothers with EIBF, especially in rural areas. Targeted interventions, such as training programs and supportive supervision, are necessary to enhance midwives' skills and confidence in promoting and supporting EIBF.